Vicarious Posttraumatic Growth Pada Perawat Gawat Darurat Yang Terindikasi Secondary Traumatic Stress - Redebire, Bintang Denezia (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2025)
This study aims to explore the dynamics of Vicarious Posttraumatic Growth (VPTG) among Emergency Room nurses who experience Secondary Traumatic Stress (STS). A qualitative method with a phenomenological approach was employed. Data were collected through in-depth interviews with three male nurses aged 30–34 and analyzed using MAXQDA software. Findings revealed that participants experienced STS due to exposure to patient deaths, traumatic injuries, medical procedure failures, and family pressure. Nonetheless, they also demonstrated positive growth, including increased empathy, personal strength, new life plans, and spiritual change. Social support and professional training facilitated this growth, while excessive workload and unresolved trauma acted as barriers. These results suggest that despite STS pressures, nurses have the capacity for psychological growth when supported by a conducive environment and adaptive coping strategies.